Idræt og velfærd i et historisk perspektiv. En fortælling om gensidig afhængighed - Trangbæk, Else (Forum for Idræt, 2011)
Artiklen reflekterer over de normer og forventninger, der har været og styrer den politiske tækning i forhold til idræt og velfærdspolitik. Idrættens autonomi diskuteres desuden. In recent years, the welfare state and the welfare model have been put on the political agenda in Denmark. Some politicians argue that the state has to reduce the costs for welfare, not least because of the increasing expenses caused by the increasing life expectancy of the population. Others believe that the »burden« should be shifted from the government to the civil society or the market. Despite disagreements, there is quite a large consensus that the welfare state has to be preserved, but that it must be reassessed. The article reflects the norms and expectations that have been and still are the basis of political reflections about the Danish sports and welfare policy. In addition, it is argued that the focus on the autonomy of sport should be replaced by a dialogue and an analysis of the interdependence of sport and welfare.